Carbon Disclosure and Firm Performance: The Role of the Upper Echelons - Ega Annisa Rizti; Cynthia Afriani Utama (AFEBI Management and Business Review, 2022)
The characteristics of the upper echelons reflect the propensity of firms to disclose their carbon. This study examines gender diversity and family ownership in Indonesia as the instrumental variables in mediating the relationship between carbon disclosure and firm performance. The sample consists of 423 firm-year observations from 2008 to 2020. The findings validate gender diversity and family firm as instrumental variables. Women within the Board of Commissionaires (BoC) and the Board of Directors (BoD) positively impact carbon disclosure, while family firms are found to disclose less. Furthermore, the supervisory function of the BoC has a positive effect on carbon disclosure in companies with low carbon disclosure scores, while companies with high scores are more prone to strategies adopted by the BoD. This research contributes to prolong the discussion about which upper echelons’ characteristics influence carbon disclosure.